Pengaruh Pemberian Trichoderma sp Terhadap Pertumbuhan Dan Hasil Tanaman Cabai Merah (Capsicum annum L.) - Thesiwati, Aslan Sari (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2019)
The purpose of this experiment was to know the effect of giving Trichoderma spagainst the growth and yield of the red chili plants (Capsicum annum L).his research was conducted on the experimental land of Tamansiswa University in Ampang Village, Kuranji District, Padang Cityto place height 10 m above sea level. This research was conducted from February to May 2018. This study uses a Completely Randomized Design (CRD) consisting of 5 levels, namely: 0 gr/polybag, 25 gr/polybag, 50 gr/polybag, 75 gr/polybag and 100 gr/polybag. The observation data was analyzed by means of variance statistics and DNMRT follow-up tests at the levels of 5% and 1%. Based on the results of the study it can be concluded that the administration of Trichoderma sp at a rate of 0-100 gr / polybag has no significant effect on the growth of chili plants while 75 gr / polybag has a significant effect on the number of fruit crops and fruit weight. Based on the research it is recommended that the cultivation of red chili plants use Trichoderma sp at a dose of 75 gr / plant.